PSVIII-32 Late-Breaking Abstract: The effect of outdoor stocking density and weather on the behavior of broiler chickens raised in mobile shelters on pasture. (30th November 2020) - Heins, Brad J; Phillips, Hannah
Abstract: The aim of this study was to examine the behavior, and the relationship between weather and behavior, of broilers raised in mobile shelters with two stocking densities of pasture access. Fifty straight-run Freedom Rangers were used in three replicates (n = 150) at the University of Minnesota West Central Research and Outreach Center (Morris, MN). From 4 to 11 weeks of age, birds were housed in a mobile shelter divided into two equal-sized pens with daily access to pasture. Birds were allocated to one of the two pens corresponding to the treatment groups: 1) high (0.46 m 2 per bird) and 2) low (2.5 m 2 per bird) density outdoor pasture allowance. Ten focal birds per pen were randomly designated for behavior observations performed eight times weekly from 5 to 10 weeks of age. Counts of the number of birds outside were recorded during each observation. Behaviors were recorded continuously for 1-minute durations (Animal Behaviour Pro© app) on each focal bird. The means averaged for each observation were analyzed in linear mixed models with fixed (treatment), random (pen and replicate), and repeated (observation) effects. Models included age, heat index, solar radiation, and their interactions with treatment based on a backward stepwise selection. The temperature range recorded during the study was 7 to 32 ⁰C. No behavioral differences between treatments were observed. Standing decreased (P < 0.05) as heat index increased. Pasture use declined (P < 0.05) when heat index was greater than 26 ⁰C. Foraging decreased (P < 0.05) and pasture use increased (P < 0.05) as age increased. The results of this study indicate similar behaviors of broilers raised with two levels of pasture allowance and suggests that hot weather negatively affects the use of pasture space. Thus, providing shade in pasture might be a method to increasing ranging in broilers.